2022
DOI: 10.2147/jpr.s365187
|View full text |Cite
|
Sign up to set email alerts
|

Association of Biomarkers with Individual and Multiple Body Sites of Pain: The Johnston County Osteoarthritis Project

Abstract: Introduction Biochemical biomarkers may provide insight into musculoskeletal pain reported at individual or multiple body sites. The purpose of this study was to determine if biomarkers or pressure-pain threshold (PPT) were associated with individual or multiple sites of pain. Methods This cross-sectional analysis included 689 community-based participants. Self-reported symptoms (ie, pain, aching, or stiffness) were ascertained about the neck, upper back/thoracic, low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…41 A study with 689 participants found no association between IL-6 plasma concentration and chronic hip, shoulder, and neck pain. 35 The results of our research suggested that targeting the IL-6 pathway could potentially reduce the risk of developing chronic back and knee pain. It is important to exercise caution when interpreting these findings, as the effects of targeting the IL-6 pathway specifically on chronic pain intensity and duration are still unknown.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…41 A study with 689 participants found no association between IL-6 plasma concentration and chronic hip, shoulder, and neck pain. 35 The results of our research suggested that targeting the IL-6 pathway could potentially reduce the risk of developing chronic back and knee pain. It is important to exercise caution when interpreting these findings, as the effects of targeting the IL-6 pathway specifically on chronic pain intensity and duration are still unknown.…”
mentioning
confidence: 76%
“…Although not as well-established as the correlation found between variation at IL6R and specific health outcomes, previous studies have reported phenotypic implications associated with variations in gp130. 25,26 We aimed to develop genetic instruments using a recent Genome-Wide Association Study (GWAS) involving 35,287 participants from the DECODE consortium. 27 We extracted 24 independent SNPs (with a P-value lower than 5*10 −8 and an r2 below 0.1) and linked to gp130 levels within a range of 300 kb of the gp130 area (Table S6).…”
Section: Cisgp130 Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Norman et al. investigated the relationship between inflammation biomarkers and musculoskeletal pain, revealing no significant association between RANTES and shoulder pain ( 33 ). Despite this, direct studies on the relationship between RANTES and AC are limited, warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%